5 Serious conditions among patients with non-specific chief complaints in the pre-hospital setting. A retrospective cohort study. (26th April 2019) - Ivic, R; Kurland, L; Vicente, V; Castrén, M; Bohm, K
Abstract : Background: Non-specific complaints (NSC) are common presentations to the emergency medical services (EMS). Patients with NSC often present with normal vital signs. Also, among patients with NSCs approximately one third have serious conditions which are not identified. Patients with NSC's are poorly studied in the pre-hospital setting. The aim of the current study was to describe the outcome serious condition in patients presenting with non-specific chief complaints to the EMS. Method: A retrospective cohort study of all patients≥18 years, reported as presenting with NSC to the EMS in Stockholm County and transported to an emergency department. Patients were identified via EMS electronic patient record and followed via national patient registers. The outcome serious condition was defined in consensus. Descriptive statistics and regression analyses were performed. Results: 3780 patients were included. Median age was 77 years. Serious conditions were present in 1334 (35.3%) of the patients. Admission to in-hospital care rate was 67.6%. The in-hospital mortality rate was 135 (10.1%) (OR 6.6 CI 95% 3.5–12.5) and 30 day mortality was 269 (20.2%) (OR 4.4 CI 95% 3.3–5.7) in the group with serious conditions compared to 25 (1.0%) and 103 (4.2%), respectively, for the group with no serious conditions. Elevated triage levels by rapid emergency triage and treatment system (RETTS) was associated with serious condition as well as mortality rates. Conclusion: One third of the patients presenting with NSC in the pre-hospital setting have an underlying serious condition which is associated with in-hospital admission and risk of death. Conflict of interest: None. Funding: None.